Research on Power Coordination Control Strategy of Microgrid Based on Reconfigurable Energy Storage - Xiaoxi Liu; Libo Jiang; Tianwen Zheng; Zhengwei Zhu (Energies)
Reconfigurable new energy storage can effectively address the security and limitation issues associated with traditional battery energy storage. To enhance the reliability of the microgrid system and ensure power balance among generation units, this paper proposes a power coordination control strategy based on reconfigurable energy storage. First, a new microgrid system incorporating reconfigurable energy storage, photovoltaic power generation, and a supercapacitor is introduced. By leveraging the structural advantages of reconfigurable energy storage, the potential safety hazards of traditional battery energy storage can be mitigated and the reliability of the microgrid system can be improved. Second, a novel control strategy for reconfigurable energy storage, photovoltaic units, and supercapacitors is proposed. The reconfigurable energy storage achieves constant current charge/discharge control through a DC-DC converter, while the supercapacitor maintains DC bus voltage stability via another DC–DC converter. Next, the power flow relationship within the microgrid system is analyzed. The dynamic reconfiguration characteristics of the reconfigurable energy storage, combined with the high power density of the supercapacitor, enable dynamic compensation of the photovoltaic power generation unit to meet the load’s power demand. Finally, a simulation model is developed in the MATLAB/Simulink environment to compare and analyze the power compensation effects of traditional energy storage and reconfigurable energy storage. The results demonstrate that the proposed control strategy achieves constant current charge/discharge control for reconfigurable energy storage, addressing the issue of battery life degradation caused by the continuous variation in charge/discharge current when traditional energy storage compensates for photovoltaic fluctuations. Additionally, the proposed control strategy can effectively and rapidly adjust the system’s power output, mitigating power fluctuations caused by variations in photovoltaic generation and load changes in the microgrid system, thereby improving the system’s reliability and stability.